2008
DOI: 10.4103/0250-474x.43012
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of <i> Terminalia catappa</i>, <i> Manilkara zapota</i> and <i> Piper betel</i> leaf extract

Abstract: Aqueous and methanol extract of the leaves of Terminalia catappa L., Manilkara zapota L. and Piper betel L. were evaluated for antibacterial activity against 10 Gram positive, 12 Gram negative bacteria and one fungal strain, Candida tropicalis. Piperacillin and gentamicin were used as standards for antibacterial assay, while fluconazole was used as standard for antifungal assay. The three plants showed different degree of activity against the microorganisms investigated. The methanolic extract was considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The agar well diffusion method was used to test the anti-microbial effect of N. sativa crude extracts [27] . All media plates (9 cm in diameter) were prepared according to the manufacturer recommendations (Difco Laboratories, USA).…”
Section: Agar Well Diffusion Assaymentioning
confidence: 99%
“…The agar well diffusion method was used to test the anti-microbial effect of N. sativa crude extracts [27] . All media plates (9 cm in diameter) were prepared according to the manufacturer recommendations (Difco Laboratories, USA).…”
Section: Agar Well Diffusion Assaymentioning
confidence: 99%
“…plant has been investigated in various pharmaceutical studies as it contains a variety of chemical components (Pandya et al, 2013; Yeh et al, 2014). T. catappa L. leaf extracts exhibit biological activities, including antioxidant (punicalagin, punicalin, terfluvina A and B, chebulic acid, benzoic acid, cumaric, and its derivatives) (Chen and Li, 2006; Chyau et al, 2006; Kinoshita et al, 2007), antidiabetic (β-carotene) (Anand et al, 2015), anticancer (punicalagin) (Naitik et al, 2012), antiviral (ellagic acid) (Tan et al, 1991), anti-inflammatory (triterpenic acids, especially ursolicacid and its derivatives) (Fan et al, 2004), antimicrobial (flavones and flavanols) (Kloucek et al, 2005; Nair and Chanda, 2008; Shinde et al, 2009), and hepato-protective activities (punicalagin, punicalin) (Kinoshita et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In India, a plaster of T. catappa leaves is used to treat scabies, leprosy wounds and other skin diseases (Nair and Chanda, 2008). Its traditional use includes the treatment of diarrhea and fever, especially in India, the Philippines and Malaysia (Kloucek et al, 2005; Shinde et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The methanolic extract is significantly more efficient than the aqueous extract in inhibiting the investigated microbial strains. [6] Shikhamandloi et al [4] found that the methanolic extract shows antifungal activity against Curvularia lunata , Aspergillus niger , Penicillium chrysogenum , and Trichophyton tonsurans .…”
Section: Botanical Descriptionmentioning
confidence: 99%